1983
DOI: 10.1002/cm.970030208
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of cAMP with modeled bull sperm

Abstract: Demembranated and membrane disrupted bull sperm models exhibit an increase in motility when exposed to cAMP. Tritium-labeled cAMP was used to locate the initial site of action of cAMP in the modeled sperm preparations. cAMP did not bind selectively to the modeled cells, and the presence or absence of plasma membrane fragments on the models did not significantly alter this result. When suspension medium taken from modeled sperm preparations was subjected to gel filtration on Sephadex G25-150 columns, cAMP bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The binding of cAMP to its regulatory subunit in bull sperm is competitively inhibited by cGMP, indicating both interact at the same binding site [96]. cAMP and cGMP do not appear to have identical effects on the Ca2' -mediated curvature response in rat sperm flagella [92], which is consistent with the Ca2' response of Paramecium cilia [15].…”
Section: Other Regulatory Factorsmentioning
confidence: 76%
See 1 more Smart Citation
“…The binding of cAMP to its regulatory subunit in bull sperm is competitively inhibited by cGMP, indicating both interact at the same binding site [96]. cAMP and cGMP do not appear to have identical effects on the Ca2' -mediated curvature response in rat sperm flagella [92], which is consistent with the Ca2' response of Paramecium cilia [15].…”
Section: Other Regulatory Factorsmentioning
confidence: 76%
“…A soluble 56 kilodalton phosphoprotein called axokinin seems to play a key role in mediating the cAMP response [147,1481. Consistently, removal of the cytosol from sperm models renders the sperm incapable of responding to cAMP [96]. This suggests that some component of the cytosol, either axokinin or the 49 kilodalton Type I regulatory subunit of CAMP-dependent kinase (RI) that is removed by detergent extraction [76], is required for the cAMP response.…”
Section: Action Of Campmentioning
confidence: 99%
“…Similar patterns have been observed in bull (Cascieri et al, 1976), hamster (Morton et al, 1974), and guinea pig (Mukica et al, 1991) sperm in which quiescent epididymal sperm were stimulated by dilution. Furthermore, Lindemann et al (1983) found that theophylline treatment prior to demembranation and motility reactivation reduced the sperms' responsiveness to CAMP, suggesting that CAMP-dependent phosphorylation of motility-associated proteins was not necessary. However, the amount of free CAMPdependent protein kinase regulatory subunits was no different in control or theophylline-treated cells, indicating that the activation of CAMP-dependent protein kinases, like the pulse of cAMP produced by CB-V treatment, is quite shortlived.…”
Section: Discussionmentioning
confidence: 98%
“…Demembranation-reactivation experiments (Lindemann et al, 1983;Yeung, 1984) have firmly established the requirement for cAMP in mammalian sperm motility initiation and maintenance. The abundance of protein kinase A and a wide variety of phosphorylated axonemal proteins, as well as an apparent constitutive cAMP production, provide the basic elements for the control of motility through CAMP-dependent protein phosphorylation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation